Seller Perception Analysis on Purchase Decision Using Analytical Hierarchy Process Method : (Case Study: ABC Store) - Khusna Dwijayanti (Journal of Industrial Engineering and Halal Industries, 2022)
Purchasing decisions can be used as a competitive advantage for companies or retailer. Purchasing decisions are important aspects of consumer behavior to determine or make a decision whether to buy a product or not. Price, product quality, service quality, and social media promotion can be good strategies to win over existing competitors. There are many studies on consumer perception, and a few studies on seller perception. Therefore, this study aims to analyze the effect of price, product quality, service quality, and social media promotion on purchasing decisions at ABC Store by measuring the perceptions of the sellers. The questionnaires in this study are given to sellers and marketing managers who are experienced in selling the product. The analysis conducted using Analytical Hierarchy Process (AHP). The results of this study indicate that from the perception of the seller, the order of importance that influences the purchase decision for gadget at ABC Store is social media promotion 30%, price 28%, product quality 26%, and lastly service quality 15%.